An alternative formation mechanism of {332}BCC twinning in metastable body-centered-cubic high entropy alloy. (August 2022) - Gao, Junheng; Huang, Yuhe; Hu, Xiaogang; Wang, Shuize; Rainforth, W. Mark; Todd, Iain; Zhu, Qiang
Abstract: In this work, the origin of {332}BCC twinning was investigated in a body-centered-cubic (BCC) high entropy alloy (TiZrHf)87 Ta13 (at.%). Detailed transmission electron microscopy analysis of the deformed microstructure revealed that a special ''{351}''< 2 ¯ 11 >α" type II twinning generates in the early deformation stage, and with further straining, the ''{351}''< 2 ¯ 11 >α" type II twin variant accommodates into a {351}α" type I twin variant. The resultant {351}α" type I twinning exhibits good lattice correspondence with the {332}BCC twinning and further propagates into the retained BCC grain with orientation relationship of {351}α" //(332)BCC, structuring into a {332}BCC twin-like configuration. Based on the experimental results and twinning analysis through evaluating twinning shear and atomic shuffle mechanism of this specific feature, our findings provide an alternative mechanism for the formation of {332}BCC twinning in which a special martensitic type II to type I twinning transformation mechanism took effect. Graphical abstract: Image, graphical abstract